Preservation state of the sound and audiovisual documents in libraries of research institutes and centers of the National Autonomous University of México - Rodríguez Reséndiz, Perla Olivia (Revista General de Información y Documentación, 2019)
The libraries, like others memory institutions, have the challenge of preserving sound and audiovisual documents recorded on analog carriers and born digital. This task is complex because until now the preservation of print materials has been privileged. However, it offers opportunities for libraries that have not yet started this task. This paper presents the questionnaire results about preservation state in libraries of research institutes and centers of science and humanities of the UNAM. It presents the situation and perspectives of analog and born digital sound and audiovisual collections; the advances in the digitalization and the digital preservation tools used to guarantee the long term permancen of these materials. To conclude, it stablishes a challenges to take in consideration for the libraries.